Cartilage Repair: Injectable Cholesterol‐Enhanced Stereocomplex Polylactide Thermogel Loading Chondrocytes for Optimized Cartilage Regeneration (Adv. Healthcare Mater. 14/2019). Issue 14 (25th July 2019) - Wang, Chenyu; Feng, Naibo; Chang, Fei; Wang, Jincheng; Yuan, Baoming; Cheng, Yilong; Liu, He; Yu, Jiakuo; Zou, Jun; Ding, Jianxun; Chen, Xuesi
Abstract : Scaffolds are a critical factor of cartilage tissue engineering. In article number1900312, Yilong Cheng, He Liu, Jun Zou, Jianxun Ding, and co‐workers develop a cholesterol‐modified stereocomplex thermogel of four‐arm poly(ethylene glycol)–polylactide with appropriate critical gelation temperature, mechanical strength, pore size, degradation, and chondrocyte adhesion for optimized cartilage regeneration. Cover design by He Liu and Jianxun Ding.